The Influence of Islamic Counseling Guidance and Peer Support on Students’ Mental Resilience at Uswatun Hasanah Islamic Junior High School, Jambi City - Hasan, Zulfahmi; Agustianda; An Nu’man; Muhammad Alvin Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to determine the influence of Islamic Counseling Guidance and Peer Support on the Mental Resilience of students at SMP Islam Uswatun Hasanah Kota Jambi. This research employed a quantitative approach with a correlational research design. The population consisted of 148 students, while the sample included 55 students. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using multiple linear regression with the assistance of SPSS through classical assumption tests, t-tests, F-tests, and coefficient of determination analysis. The results showed that Islamic Counseling Guidance had a significant effect on Students’ Mental Resilience with a significance value of 0.000 < 0.05. Peer Support also had a significant effect on Students’ Mental Resilience with a significance value of 0.028 < 0.05. Simultaneously, Islamic Counseling Guidance and Peer Support significantly influenced Students’ Mental Resilience with an F value of 20.980 and a significance value of 0.000 < 0.05. The coefficient of determination (R Square) of 0.447 indicates that Islamic Counseling Guidance and Peer Support contributed 44.7% to Students’ Mental Resilience, while the remaining 55.3% was influenced by other factors outside this study. Based on the findings, it can be concluded that Islamic Counseling Guidance and Peer Support have a positive and significant influence on the Mental Resilience of students at SMP Islam Uswatun Hasanah Kota Jambi.